Epitheliocystis Distribution and Characterization in Brown Trout (Salmo trutta) from the Headwaters of Two Major European Rivers, the Rhine and Rhone - Guevara Soto, Maricruz; Vaughan, Lloyd; Segner, Helmut; Wahli, Thomas; Vidondo, Beatriz; Schmidt-Posthaus, Heike (Frontiers in Physiology, 2016)
We present a first description of the distribution and characterization of epitheliocystis infections in brown trout (Salmo trutta) from the upper catchments of two major European rivers, the Rhine and the Rhone. Overall, epitheliocystis was widely distributed, with 70% of the Rhine and 67% of the Rhone sites harboring epitheliocystis positive brown trout. The epitheliocystis agents Candidatus Piscichlamydia salmonis and Candidatus Clavichlamydia salmonicola could be identified in both catchments, although their relative proportions differed from site to site. Additionally, in two rivers in the Rhine catchment, a new species of Candidatus Similichlamydia was identified. Based on the histology, infection intensity and severity of pathological changes were significantly more pronounced in mixed chlamydial infections, whereas single infections showed only low numbers of cysts and mild pathology. Infections could be found over a wide range of temperatures, which showed no correlation to infection prevalence or intensity.